2007
DOI: 10.1016/j.baae.2006.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Species abundances influence the net biodiversity effect in mixtures of two plant species

Abstract: Species abundances (evenness or identity of the dominant species in mixtures) usually are not rigorously controlled when testing relationships between plant production and species richness and may be highly dynamic in disturbed or early successional communities. Changes in species abundances may affect the yield of mixtures relative to yields expected from species monocultures [the net biodiversity effect (NBE)] by changing how species that differ in function are distributed in the plant community. To test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…Previous theoretical work found that unevenness can indeed weaken biodiversity-stability relationships [9,22], because the most diverse components of a community, namely rare species, may have limited effects on community stability owing to their low abundances [51]. This theoretical prediction is supported by a growing number of experimental investigations, as well as the current study, showing weak or non-significant biodiversity-stability relationships when dominant species regulate community stability [32][33][34][52][53][54][55]. In the present study, the dominant species as royalsocietypublishing.org/journal/rspb Proc.…”
Section: (A) Biotic Stability Mechanisms and The Importance Of Dominant Species In Grasslands Of Inner Mongoliasupporting
confidence: 80%
“…Previous theoretical work found that unevenness can indeed weaken biodiversity-stability relationships [9,22], because the most diverse components of a community, namely rare species, may have limited effects on community stability owing to their low abundances [51]. This theoretical prediction is supported by a growing number of experimental investigations, as well as the current study, showing weak or non-significant biodiversity-stability relationships when dominant species regulate community stability [32][33][34][52][53][54][55]. In the present study, the dominant species as royalsocietypublishing.org/journal/rspb Proc.…”
Section: (A) Biotic Stability Mechanisms and The Importance Of Dominant Species In Grasslands Of Inner Mongoliasupporting
confidence: 80%
“…Among our most interesting findings was the negative relationship between standing biomass and both species and functional evenness (FEve). Both niche complementarity and facilitative effects can be the strongest at high evenness levels 75,76 , as evenness determines the relative importance of inter- vs. intraspecific interactions 45 . Intraspecific competition is expected to be more intense than interspecific competition and the increased level of species evenness (i.e.…”
Section: Discussionmentioning
confidence: 99%